The Yin and Yang of Copper During Infection - Besold, Angelique N. (J Biol Inorg Chem, 2016)
Copper is an essential micronutrient for both pathogens and the animal hosts they infect. However, copper can also be toxic in cells due to its redox properties and ability to disrupt active sites of metalloproteins, such as Fe-S enzymes. Through these toxic properties, copper is an effective antimicrobial agent and an emerging concept in innate immunity is that the animal host intentionally exploits copper toxicity in antimicrobial weaponry. In particular, macrophages can attack invading microbes with high copper and this metal is also elevated at sites of lung infection. In addition, copper levels in serum rise during infection with a wide array of pathogens. To defend against this toxic copper, the microbial intruder is equipped with a battery of copper detoxification defenses that promote survival in the host, including copper exporting ATPases and copper binding metallothioneins. However, it is important to remember that copper is also an essential nutrient for microbial pathogens and serves as important cofactor for enzymes such as cytochrome c oxidase for respiration, superoxide dismutase for anti-oxidant defense and multi-copper oxidases that act on metals and organic substrates. We therefore posit that the animal host can also thwart pathogen growth by limiting their copper nutrients, similar to the well-documented nutritional immunity effects for starving microbes of essential zinc, manganese and iron micronutrients. This review provides both sides of the copper story and evaluates how the host can exploit either copper-the-toxin or copper-the-nutrient in antimicrobial tactics at the host-pathogen battleground.